The Perception of Petra Christian University Students Towards the Connection Between “Converse” Brand and Its “Proud to Be” Statement on Its T-Shirt Line - Samuelita Dayu Maharani (Kata Kita: Journal of Language, Literature, and Teaching, 2018)
This thesis mainly deals with the theory of perception and decoding process to observe how Petra Christian University students perceive the connection between Converse brand and the use of  language in one of its T-shirt products, “Proud to be”. From the analysis, the researcher found out that the students could draw a line between the brand and its statement on its T-shirt design. This means that “Proud to be” statement is considered a success as a code to express the company’s message to its consumers and suits the brand personality of Converse. In conclusion, the language used in product design is able to communicate the brand personality.